Clinical Application of a Real-Time Telepathology System for Frozen Section Diagnosis in Comparison With Optical Microscope - Huang, Yu Ting; Renne, Salvatore Lorenzo; Sollai, Mauro; Damiani, Domenico; Bossi, Paola; Morenghi, Emanuela; Roncalli, Massimo; Di Tommaso, Luca (Frontiers in Medicine, 2019)
Background. The imbalance between the increasing demand of highly specialized service and the reduction of specialists able to release this service, is a global challenge for Pathology. This situation applies also to the setting of intra-operatory diagnostic: here the broad presence of Surgical divisions contrasts with the contraction of Pathology departments, progressively concentrated in few hospitals. The use of e-pathology device, such as remote-control microscopes, offers a possible solution to this imbalance. Aim. To prove the non-inferiority of function of a remote-control, real-time microscope named Nano-Eye Device (NED) with the optical microscope (OM) for intra-operatory histological diagnosis. Methods. The study was designed into two phases: discovery and validation. During the discovery phase features influencing the process of adaptation to NED were investigated in detail, focusing on the turnaround time (TAT). Validation phase investigated the diagnostic concordance between NED and OM; as well as sensitivity, specificity and accuracy of NED in intra-operatory histological diagnosis. Results. During the discovery phase 250 cases were examined. TAT of NED was longer than that of OM (112 ± 89.8 versus 36 ± 37.9 seconds) and influenced by the difficulty of the specimen, age of pathologist and the type of the specimen. In the validation phase (185 cases) TAT of NED reduced significantly to 92 ± 86.3 sec (p: 0.01). NED showed a concordance rate of 98% with OM; the sensitivity 95.65%), specificity (100%) and diagnostic accuracy (98.87%) of NED were equal to that of OM. NED failed to work in 6% during the discovery phase and 4% in the validation. Conclusions. Taken as a whole, the functionality of NED is comparable to OM. It can be the alternative choice for hospital lacking on-site pathology services and one of the tool of e-pathology.